2021
DOI: 10.3390/en15010029
|View full text |Cite
|
Sign up to set email alerts
|

Inertia Control Strategy of DFIG-Based Wind Turbines Considering Low-Frequency Oscillation Suppression

Abstract: It has become a basic requirement for wind turbines (WTs) to provide frequency regulation and inertia support. The influence of WTs on the low-frequency oscillation (LFO) of the system will change after adopting inertia control methods. This paper intends to investigate and compare in detail the IC effects on LFO characteristics in two systems with different structures. First, the mechanism of inertia control of doubly fed induction generator (DFIG)-based WTs is analyzed. Then, the small-signal analysis method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Coordinated VI allocation is implemented based on inertia demand in a WT-based power system network [59]. Different optimisation techniques have been used to optimise the VI control parameters with a coordinated derivative control scheme [60]. The simulation is carried out using EMT platforms.…”
Section: Traditional Strategiesmentioning
confidence: 99%
“…Coordinated VI allocation is implemented based on inertia demand in a WT-based power system network [59]. Different optimisation techniques have been used to optimise the VI control parameters with a coordinated derivative control scheme [60]. The simulation is carried out using EMT platforms.…”
Section: Traditional Strategiesmentioning
confidence: 99%
“…Energies 2022, 15, x FOR PEER REVIEW 3 of 35 2. Small-perturbation angle stability: To evaluate the power system stability when small variations in loads and generation occur, as continuously happens in a real scenario, not necessarily related to a transient disturbance.…”
Section: Network Model and Scenariosmentioning
confidence: 99%
“…Academic and industrial research studies have been (and are) extensively active in proposing methods and technologies able to transform RESs and loads into sources of flexibility by modifying their control procedures and/or combining them with Battery Energy Storage Systems (BESSs). More specifically: in [2][3][4] the authors propose control strategies to enable wind generators to provide Synthetic Inertia (SI); in [5] wind generators are made capable to provide primary droop frequency regulation; in [6,7] converter-interfaced generators are designed to provide SI; in [8][9][10] aggregates of thermal loads are controlled Energies 2022, 15, 3517 2 of 33 to provide primary and secondary frequency regulation services; in [11] a control strategy for a building air cooling system that provides secondary frequency regulation is experimentally validated; in [12] multiple BESSs are controlled to provide frequency regulation; in [13] BESSs are coupled with wind generators to provide frequency regulation services; in [14] a BESS is coupled with a large scale photovoltaic (PV) generator to provide primary frequency regulation; in [15] a decentralized control strategy is proposed to allow wind generators to provide primary voltage regulation; in [16] primary voltage regulation is realized by multiple BESSs via broadcast control at subtransmission level, while [17] generalizes this technique for any type of RES, applies it at distribution network level, upgrades it with an additional coordination level and compares it against centralized optimal reactive power control; in [18,19] voltage regulation is realized through DSR considering residential loads; in [20] voltage regulation performance form Distributed Energy Resources (DERs) are validated by Hardware-in-the-Loop simulations; in [21,22] voltage regulation is realized by PV generators; in [23] a chance-constrained optimization method is proposed to provide voltage regulation by DERs; in [24] voltage regulation is provided by distributed BESSs via reinforcement learning.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of inertial response provision from DFIGs on small-signal stability was investigated by [24], and the authors concluded that the effect can be either positive or negative, depending on the control parameters. However, the intertwining effects between inertial and frequency support and the impact on converter-control based oscillations were neglected.…”
Section: Introductionmentioning
confidence: 99%